Pengaruh Likuiditas, Profitabilitas dan Leverage Terhadap Return Saham Perusahaan Manufaktur Sektor Barang Konsumsi yang Terdaftar di Bursa Efek Indonesia Tahun 2018-2020 - fitri veronika; Batara Daniel Bagana (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2023)
This study aims to examine the effect of liquidity, profitability and leverage on stock returns. This research was conducted using secondary data. The population in this study are manufacturing companies in the Consumer Goods Sector that are listed on the Indonesia Stock Exchange (IDX) for 2018-2020. Sampling using purposive sampling. Data analysis technique using Multiple Linear Regression Analysis. The results of the study show that Liquidity (CR) has a significant positive effect on stock returns in manufacturing companies in the consumer goods sector that are listed on the IDX in 2018-2020. Profitability (ROA) has a significant positive effect on stock returns in manufacturing companies in the consumer goods sector listed on the IDX in 2018-2020. Leverage (DER) has a negative effect on stock returns.